Evaluation of essential oils from Boswellia sacra and Teucrium mascatense against acetyl cholinesterase enzyme and urease enzyme - Ghulam Abbas,; Muhammad Abdullah Albroumi,; Najeeb Ur Rehman,; Hidayat Hussain,; Ahmed Sulaiman Al-Harrasi, (International Journal of Phytomedicine, 2016)
Enzyme inhibition is one of the most important areas of pharmaceutical research which resulted in the discoveries of several useful drugs. The prime aim of this study is to identify effective natural inhibitors against pharmacologically important enzymes such as acetylcholinesterase enzyme and urease enzyme. In present study, we evaluated the essential oils extracted from medicinally important plants including Boswellia sacra Flückiger (frankincense) and Teucrium mascatense Boiss. Two major constituents of frankincense essential oil including (+)-α-pinene and (R)-+-limonene were also investigated against these enzymes. The essential oils were extracted from Boswellia sacra and Teucrium mascatense which are native plants to the southern and northern areas of Oman, respectively. In this study, the essential oil of frankincense exhibited significant inhibition with IC50 value of 0.043±0.02 mg/mL, against acetylcholinesterase enzyme while against urease enzyme it has shown good inhibition with IC50 value of 0.17 ± 0.05 mg/mL. The essential oil obtained from the Teucrium mascatense was found to be in active against both the enzymes. On acetylcholinesterase enzyme inhibition assay, the (+)-α- pinene exhibited significant inhibition (IC50 = 0.094±0.01 mg/mL) while (R)-+- limonene was found to be inactive on this assay. Against urease enzyme (+)-α- pinene and (R)-+- limonene showed moderate activity 40.06±1.03 % and 19.5±1.00 %, respectively. Interestingly, the mixture of equal concentration of (+)-α- pinene and (R)-+- limonene exhibited 70% inhibition with IC50 value of (0.195 ± 0.10 mg/mL) which shows the synergistic relationship between them. Promising inhibitory potential of frankincense essential oil and (+)-α-pinene, against acetylcholinesterase enzyme and urease enzyme indicated their potential therapeutic role to manage Alzheimer’s disease and stomach ulcers, respectively.